Lower-body strength, power and sprint front crawl performance - Muniz-Pardos Borja; Gomez-Bruton Alejandro; Matute-Llorente Angel; Gonzalez-Aguero Alex; Olmedillas Hugo; Gomez-Cabello Alba; Casajus Jose A.; Vicente-Rodríguez Germán (Translational Exercise Biomedicine, 2024)
To determine the association between lower-body strength and lower-body power capacities with sprint swimming performance in adolescent competitive swimmers.